Estudo de diversidade genética e efeito inibitório do látex de Calotropis procera em fungos fitopatogênicos - Silva, Shamyra Georgia de Azevedo e (Universidade Federal Rural do Semi-Árido, 2015)
Silk Flower [Calotropis procera (Aiton) W.T. Aiton] is a plant that has been highlighted by the case of a species that has several features such as animal feed, traditional medicine, agriculture, environment, cosmetics and textile industry, and may also act to combat pests, fungi and viruses through mechanisms defense associated with your latex. This study aimed to evaluate latex fluid from Silk Flower in inhibiting the development of pathogenic fungi of Macrophomina phaseolina, Rhizoctonia solani, Colletotrichum musae and Monosporascus cannonballus and study the genetic diversity from Silk Flower genotypes using the RAPD and ISSR molecular markers. Twenty samples of species of leaves were collected in the Grossos/RN and Mossoró/RN cities (ten plants from each city). The plants latex were tested on four different types of phytopathogenic fungi, Macrophomina phaseolina, Rhizoctonia solani, Colletotrichum musae and Monosporascus cannonballus with two different methods (adding latex to the culture medium before and after polymerization middle), and with two different concentration level (neat and diluted 1:1). For molecular analysis, DNA of each plant was extracted with 11 RAPD primers and 10 ISSR primers. For latex analyzes, it was observed that there was no inhibitory effect for any of Macrophomina phaseolina, Rhizoctonia solani, Colletotrichum musae and Monosporascus cannonballus isolates in any of the concentrations tested under the conditions studied. Molecular results showed a good standard for both amplification of DNA markers, showing the formation of different groups, and the presence of genetic variability has been detected. For the analysis with molecular markers there was the formation of the four distinct groups, and in the ISSR marker was observed the formation of six groups. When it was analyzed the two markers in a corresponding manner it was possible to detect the formation of seven distinct groups showing the existence of variability. The difference in the results of both markers can be explained by the case of two markers that covered different regions of the genome
Genetic diversity study and inhibitory effect of Calotropis procera latex in pathogenic fungi
Keywords: Calotropis procera; Pathogenic fungi; genetic variability; Calotropis procera; Fungos fitopatogênicos; Variabilidade genética; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA